A Scoping Study of Psychosocial Factors in Women Diagnosed With and/or Treated for Pelvic Organ Prolapse. Issue 5 (May 2020) - Touza, Kaitlin K.; Rand, Kevin L.; Carpenter, Janet S.; Chen, Chen X.; Heit, Michael H.
Abstract : Objective: Pelvic organ prolapse (POP) is prevalent and can impact women's physical and psychosocial health. To develop interventions that support this population, an understanding of the state of research on psychosocial factors related to POP is essential. We conducted a scoping study focused on the psychosocial experience of women with POP. The purpose of this review was to (1) inventory and describe the current state of knowledge of the psychosocial experience of women with POP, (2) identify gaps in knowledge, and (3) identify targets for future research. Method: Electronic databases PsycINFO, PubMed, EMBASE, and CINAHL were searched through November 1, 2017. Results: Of 524 titles reviewed, 103 articles met all inclusion criteria. Articles were grouped by the disease period (ie, prediagnosis, diagnosis/preintervention, intervention, follow-up, and mixed) and psychosocial factors. Most articles (n = 73) focused on women undergoing intervention. Articles focusing on the preintervention period was the next largest category (n = 14). Follow-up after intervention (n = 8) and samples of mixed disease periods (n = 7) were less common. One article focused on women before diagnosis. Articles focused on quality of life (QOL; n = 79), sexual function (n = 51), satisfaction (n = 16), body image (n = 13), psychological distress (n = 4), and knowledge (n = 3). Conclusions: Research on the psychosocial experience of POP has largely focused on changes in QOL and sexual function. Future research should target emotional experience of women with POP; relationships among QOL, psychological distress, body image, and sexual function; and psychosocial factors related to treatment outcomes. Abstract : A scoping study of existing literature examining psychosocial factors associated with pelvic organ prolapse.